Basic Assesment of Neck Spine Injury - -, Sri-Maliawan; Mahadewa, T. G. B (BALI MEDICAL JOURNAL, 2013)
This study aims to present a review of the basic assessment of spine and spinal cord injury. This is a review of published articles between 1978 and 2005 on the neck spine and spinal cord injury. We present a summary about the basic principles according to the literatures.
Keywords: Assesment, neck spine, injury